Uso da leitura literária na formação social do aluno da EJA em Roraima - Silva, Raquel de Paula (2017)
The present work has the objective of presenting an account of the teaching experience in the Education of Young and Adults with the accomplishment of daily activities of literary reading. The study proposes to build a theoretical framework, starting with the reading of great names of Literature, Literary Criticism, Philosophy and Sociology of Literature, thus undertaking the construction of a base of theories that support the use of literature as a means of human promotion. Another activity proposed by the work was to carry out a historical survey of the conceptions that generated the now called EJA. Promoted by social movements in favor of popular education, adult education, having as one of the great mentors and defenders Paulo Freire went through several important moments in his constitution as a modality. With the theoretical bases on literature and education established in this work, the idea of literature as a human right of Antonio Candido was therefore related to discussions about the concept of literary culture and subject reader to bring to the reflection some considerations about the process of formation of the social subject.